Оценка электромонтажных параметров коммутационных плат на ранних этапах проектирования РЭС - Elizarov, B. A.; Maksimov, A. V.; Shelest, V. I.; Shiryaev, Yu. N. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
Analytical relationships derived using methods of mathematical statistics are presented, which allow for the calculation of electrical installation parameters of switching (printed) circuit boards when placing electronic components of various sizes (ICs, microassemblies) on them during the early stages of radio-electronic equipment design, as well as during the creation of basic carrier structures.